Pelaksanaan Pembelajaran Pendidikan Agama Islam Di SD Negeri 1 Padang Panjang Barat - Lidya Lidya; Taufik Rahman; Zulfikri Zulfikri (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
Learning is the core of the educational process. In it there is interaction between various components, namely teachers, students and learning materials or learning resources. The interaction between these three main components involves facilities and infrastructure such as methods, media and the arrangement of the learning environment so as to create a learning process that allows the planned goals to be achieved. This research aims to determine the planning and implementation of Islamic Religious Education learning at Elementary School 1 Padang Panjang Barat. This type of research is qualitative research. With a descriptive qualitative method using data collection methods in the form of observation, interviews and documentation. Next, to test the validity of the data, researchers used triangulation techniques. Then, to analyze the data, researchers divided it into four components, including: data collection, data reduction, data presentation, and conclusions. The results of the research show that Islamic Religious Education Learning at Elementary School 1 Padang Panjang Before carrying out Islamic religious education learning, the teacher or educator begins by creating teaching modules and lesson boundaries. There are three learning activities carried out, namely: the teacher saying hello and prayer, student attendance and conveying the learning objectives for the preliminary activities, the teacher's core activity begins by explaining Islamic Religious Education material, and the final/closing activity begins with the students together making conclusions and the teacher giving questions and answers to the students one by one individually. random as material for evaluation and assessment of the learning of the meeting and ended with a joint prayer.